146k views
1 vote
-6(7 + t) = -24
Please answer and explain

User Viljami
by
6.4k points

2 Answers

5 votes
You want to take the -6 outside the parenthesis and multiply it by everything inside the parenthesis. So, -6*7=-42, and -6*t=-6t. Then, take the -42 and add it to both sides of the equation to get the -6t alone. -24-(-42) would become -24+42 which is 18. The new equation is -6t=18. Next, you want to get t alone by -6 on both sides of equation. 18/-6= -3, therefor t= -3. 
User Vitalii Vasylenko
by
5.7k points
6 votes
7+t= -24/-6 and two negatives make a positive so the equation changes too 7+t=24/6. You then simplify which would now be 7+t=4 because ( 24/6=4). Then subtract 7 from both sides t=4−7 and now t = -3 because 4-7=-3.
t=-3 is your answer. Hope this helped.

User Astromonerd
by
6.5k points